Adenovirus-Associated Virus Multiplication: VI. Base Composition of the Deoxyribonucleic Acid Strand Species and Strand-Specific In Vivo Transcription - Rose, J. A. (1971)
The two complementary strand species of 5-bromodeoxyuridine-substituted, adenovirus-associated virus type 2 (AAV-2) deoxyribonucleic acid were preparatively separated in CsCl density gradients and further purified by sedimentation through 5 to 20% sucrose. The base composition of each strand species was determined, and it was found that the species banding at a greater density in CsCl (heavy strands) had an expected higher thymidine content (26.5%) than that 21.7%) of the less dense species (light strands). Furthermore, the base composition of in vivo-synthesized, AAV-specific ribonucleic acid was similar to that of light-strand deoxyribonucleic acid, and this ribonucleic acid apparently hybridized only with heavy strands. These observations indicate that the heavy-strand species alone serves as the transcriptional template in vivo. This study represents the first instance in which the base composition and specificity of in vivo transcription have been determined for each of the complementary strands of an animal virus deoxyribonucleic acid.